2022
DOI: 10.3390/foods11213390
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy Based on LC-Q TRAP-MS for Determining the Distribution of Polyphenols in Different Apple Varieties

Abstract: Apples are a rich source of polyphenols in the human diet. However, the distribution of polyphenols in different apple varieties and tissues is still largely unclear. In this study, a new liquid chromatography–tandem mass spectrometry (LC-MS/MS) strategy was developed to reveal the spatial distribution of polyphenols in different apple tissues and varieties. A method based on multiple reaction monitoring (MRM)-enhanced product ion (EPI) was established in the information-dependent acquisition (IDA) mode for ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Flavonol glycosides (quercetin 3-O-glucoside, galactoside, rhamnoside and rutinoside) were mainly present in peel, while in pulp their content was low or even under the treshold of detection (quercetin 3-O-rutinoside). As Wang et al [52] reported, rutin is mainly present in the apple peel. Quercetin 3-O-galactoside and quercetin 3-O-rhamnoside were leading compounds among flavonol glycosides.…”
Section: Determination Of Polyphenolic Compounds In Applesmentioning
confidence: 92%
“…Flavonol glycosides (quercetin 3-O-glucoside, galactoside, rhamnoside and rutinoside) were mainly present in peel, while in pulp their content was low or even under the treshold of detection (quercetin 3-O-rutinoside). As Wang et al [52] reported, rutin is mainly present in the apple peel. Quercetin 3-O-galactoside and quercetin 3-O-rhamnoside were leading compounds among flavonol glycosides.…”
Section: Determination Of Polyphenolic Compounds In Applesmentioning
confidence: 92%
“…Chromatographic data acquired from the LC-Q-TOF-MS (Waters Xevo ® G2) were imported to Waters UNIFI ® for metabolites identification and binary comparison. The analysis was based on the natural products database, which was established by collecting the polyphenols and related metabolites information from the recently published literatures [10,14,20,21]. The analysis was conducted by matching the imported data file and the data processing method, in which blank, standard, QC, and experimental tests were labeled and set for three replicates.…”
Section: Data Processing and Statisticalmentioning
confidence: 99%
“…So far, several researchers have investigated the differentiation and classification of apple fruit according to the variety and/or geographical origin by using different chemometric techniques [2]. Focusing on untargeted metabolic profiles related to polyphenols, liquid chromatography quadrupole-time of flight mass spectrometry (LC-Q-TOF-MS), 1 H NMR has been applied to discriminate their difference on dried apple [8], edible part of mongo [13], sweet potato [9], coffee leaves [10] and tea [14]. Moreover, LC-Q-TOF-MS has been demonstrated to be an advanced platform for the quantification and identification of characteristic components.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phenolic compounds in apples participate in fermentation, contribute to the aroma of the fermentation juice, prevent microbial spoilage, and control the fermentation rate [ 11 , 12 ]. It has been reported that the concentration of polyphenols varies significantly among different apple varieties, with total phenolic content ranging from 107 mg/kg FW to 941 mg/kg FW [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%